Dampak Makro Ekonomi dan Faktor Internal Terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Suryakusuma Kholid Hidayatullah; Asri Nur Wahyuni (Jurnal Wira Ekonomi Mikroskil, 2018)
The performance of Islamic banking in Indonesia is currently experiencing rapid growth and growth. More and more economic actors are partnering with Islamic banking in Indonesia. Various products and services offered by Islamic banking were able to contribute positively to the financial performance of Islamic banking so that they were able to encourage the progress of the national economy. There are several variables that can affect the performance of Indonesian Islamic banking finance and in this study will conduct a research study on the influence of internal and external variables in influencing the performance of Indonesian Islamic banking finance. This study uses objects from all Islamic banking in Indonesia with the research period of 2014 to 2017. Information and financial data are obtained from annual financial reports from all Indonesian Islamic banking. The internal variables in this study use CAR, NPF, FDR, BOPO and ROA proxy. For external variables in this study using the proxy of inflation and GDP.